The interconnection between cross‒polar cap convection and the luminosity of polar cap patches. Issue 11 (8th November 2013) - Perry, G. W.; St.‒Maurice, J.‒P.; Hosokawa, K.
<x xml:space="preserve">Abstract</x> [1] The transport of patches of ionization across the polar cap is carried by the convection electric field, which imposes an E×B drift to the plasma. This drift has an upward component when the plasma is convected toward the north magnetic pole and a downward component as it moves away from the pole. The vertical motion modulates the rate at which recombination operates, which in turn is directly related to the luminosity of the patches. We show here that if a rapid increase in the electric field produces a downward velocity in excess of 10 m/s, the luminosity of the patches will at first increase before undergoing a marked decrease, in association with an increase in the recombination rates. Both the change in luminosity and the time scale for the temporary increase primarily depend on the vertical velocity, that is, on the strength of the convection electric field and on the magnetic latitude. Increases in luminosity by up to a factor of 2 or more are possible. The time scales for the variations are of the order of 10 to 20 min. We present an example of an actual luminosity modulation obtained over Resolute Bay, Canada, that agrees well with the proposed theory.